Molecular comparisons of native range collections of Gadirtha fusca, a potential biological control agent of Chinese tallowtree. Issue 8 (3rd August 2018) - Wheeler, G. S.; Dyer, K.; Broggi, E.; Ding, Jianqing; Purcell, Matthew; Madeira, P.
ABSTRACT: Chinese tallowtree, Triadica sebifera (L.) Small (Euphorbiaceae), is one of the worst invasive weeds of the southeastern USA impacting coastal wetlands, forests, and natural areas. A proposed biological control candidate, the defoliating moth Gadirtha fusca Pogue (Lepidoptera: Nolidae) shows high specificity for the target weed Chinese tallowtree. A total of 13 field sites were sampled in the native range of this herbivore species. To determine if all individuals were the same taxon, molecular DNA analyses were conducted of these collections. These included collections from 2012, 2015 and 2016, from three regions and two adult color morphs. Molecular COI analysis was performed on thirty colonized individuals from these collections. The results of this analysis arranged all taxa into a single clade with average genetic divergence values of 0.3%. Comparison of these G. fusca sequences and those from other Gadirtha spp. all had divergence values that were equal to or exceeded 5%. These results indicate that all the G. fusca collections were a single species and they were distinct from other known members of this genus.